Variants of inward disorder pattern among adolescents with different dysontogenesis - Adeeva, Tatiana; Tikhonova, Inna; Khazova, Svetlana; Sevastyanova, Ulyana; Shipova, Natalia (Special Education, 2021)
Adolescence is one of the key stages of personality development. That of adolescents with disabilities follows a non-disabled pattern. However, the process is affected by dysontogenesis, which is considered a factor that significantly affects personality development. Inward disorder pattern (IDP) is considered a complex integrative construct; a system of one’s sensations, knowledge, emotional experiences, motivation shifts caused by a disorder.IDP is considered a component of I-concept, a factor affecting its development and crucial for an individual’s functioning. Aim of the research: to identify the IDP variants of adolescents with disabilities. The sample consisted of 109 adolescents with disabilities. Their average age is 14. High indices on one or several IDP components serve to distinguish the IDP variants among adolescents. Each IDP variant is marked by respondents’ specific personal traits and I-concept features. The analysis of the ratio reveals an individual’s general behavioral pattern and attitude to their disorder. We introduce four IDP variants in the adolescent group for the moment: cognitive-emotional (tense), sensitive-cognitive (sensitive-autistic), sensitive-emotional (anxious-hypochondriac), and balanced.
Keywords: inward disorder pattern; visual impairment; speech disorders; hearing impairment; self-concept; adolescents; mental development disorder